Laser printing single gold nanoparticles - Urban, Alexander S. (2010)
Current colloidal synthesis is able to produce an extensive spectrum of nanoparticles with unique optoelectronic, magnetic, and catalytic properties. In order to exploit them in nanoscale devices, flexible methods are needed for the controlled integration of nanoparticles on surfaces with few-nanometer precision. Current technologies usually involve a combination of molecular self-assembly with surface patterning by diverse lithographic methods like UV, dip-pen, or microcontact printing.1,2 Here we demonstrate the direct laser printing of individual colloidal nanoparticles by using optical forces for positioning and the van der Waals attraction for binding them to the substrate. As a proof-of-concept, we print single spherical gold nanoparticles with a positioning precision of 50 nm. By analyzing the printing mechanism, we identify the key physical parameters controlling the method, which has the potential for the production of nanoscale devices and circuits with distinct nanoparticles.